The Influence of Context in the Subjective Evaluation of “Negative” Alcohol-Related Consequences - Merrill, Jennifer E. (Psychol Addict Behav, 2018)
College students may subjectively evaluate the consequences of drinking in unexpected ways, rating “negative” consequences as neutral or even positive experiences. We previously gathered qualitative evidence for several contextual factors that may influence one’s subjective evaluations (e.g., social influences, intoxication level, concurrent positive consequences). The purpose of the present study was to quantitatively investigate whether student evaluations of consequences differ by various contextual factors. We administered an anonymous online survey to 214 college students (76% female, 69% drinkers, 48% heavy drinkers) in return for academic credit, on which they reported how positively or negatively they would evaluate six alcohol-related consequences (e.g., vomiting, being rude, blacking out) under different conditions. Paired samples t-tests were used to compare evaluation ratings, averaged across consequences, under different hypothetical contextual conditions (e.g., among friends vs strangers). Out of 16 contextual comparisons, all but one (first-time vs repeated consequence) revealed significant differences in subjective evaluations; the pattern held in reduced samples of just drinkers or just heavy drinkers. Examples include that consequences were viewed more negatively (a) if occurring at either a party or bar vs alone in one’s home/dorm, (b) if friends express concern vs find it funny, (c) if the consequence was expected vs unexpected, and (d) if there are lasting consequences vs none. When using recent consequences in feedback-based interventions to build motivation to change, it may be useful to discuss the context of a consequence and how this influences the perceived aversiveness of that consequence.